2020
DOI: 10.37043/jura.2019.11.1.2
|View full text |Cite
|
Sign up to set email alerts
|

“Little Vienna” or “European Avant-Garde City”? Branding Narratives in a Romanian City

Abstract: By connecting the literature on urban development processes in post-socialist cities with debates from the area of place branding, this paper critically examines recent narratives of city branding in Timișoara, Romania. The aim is to investigate one specific case in the reproduction and adaptation of global urban development policies and to examine its relevance for the context of post-socialist urban politics. Our findings indicate a specific circularity between city branding and urban development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Although they are severely deprived from all kinds of state's social services, which are viewed as their rights to the city, they are not organized for demanding their rights to the city. While the existing literature showed the urban poor people's collective and organized efforts for bringing successful right to the city movements in many of the Latin American countries, like Mexico, Brazil, Chile, as well as in some European and South Asian countries (Machabanski 2013, Santos Junior 2014, Adler 2015, Málovics et al 2019, Vesalon and Crețan 2019, in the case of the urban poor of Dhaka there is hardly any such potential of RTC movements. The lack of leadership, the temporality and the uncertainty of their existence in the city are some of the valid reasons for not claiming their rights.…”
Section: Discussionmentioning
confidence: 99%
“…Although they are severely deprived from all kinds of state's social services, which are viewed as their rights to the city, they are not organized for demanding their rights to the city. While the existing literature showed the urban poor people's collective and organized efforts for bringing successful right to the city movements in many of the Latin American countries, like Mexico, Brazil, Chile, as well as in some European and South Asian countries (Machabanski 2013, Santos Junior 2014, Adler 2015, Málovics et al 2019, Vesalon and Crețan 2019, in the case of the urban poor of Dhaka there is hardly any such potential of RTC movements. The lack of leadership, the temporality and the uncertainty of their existence in the city are some of the valid reasons for not claiming their rights.…”
Section: Discussionmentioning
confidence: 99%
“…Toponymy is also shaped by political factors; due to the regime changes and/or shifts in political power, the new leaders thus use place naming and renaming as a means to assert their political authority and mold the landscape according to their socio-political and cultural image. This is observed particularly in post-Communist and neo-liberal contexts [27][28][29] and even extends to anthropic facilities such as sport stadiums and football clubs [30]. Some scholars have also found that the economic power held by large corporations shaped the landscape in terms of re-naming prominent landmarks bearing the company name of values associated with the organization [31].…”
Section: Toponymy Landscapes and Linguisticsmentioning
confidence: 99%
“…As a response to this development, countless urban planning proposals emerged to heal the everdeteriorating living conditions in the cities [1,5] (pp. [51][52][53][54]. Among many utopias, the one proposed by Ebenezer Howard-a Garden City-was based on a particular hierarchy and specific spatial order anchored in a central park or garden as an antithesis to a suburb [5] (pp.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This tendency dates back to the 1920s [15][16][17], was described in the 1930s [18] (p. 177), [19] (pp. [52][53], and the 1940s [18] (p. 177), [20] (p. 15) of the last century and was first observed on an enormous scale in the United States after World War II [1,5] (p. 76). Litwinska mentions that there is no single definition of the phenomenon of urban sprawl [15] (p. 146) and there are many, sometimes mutually exclusive, characteristics [21] (p. 108).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation